THE USE OF THERAPEUTIC COMMUNICATION TECHNIQUES IN THE INTERPERSONAL RELATIONSHIP WITH PSYCHIATRIC PATIENTS - Mariluci Alves Maftum; Maguida Costa Stefanelli (Universidade Federal do Paraná, 2000)
This study objectifies to verify if the taught contents on human and therapeutic communication increase the frequency in the use of therapeutic communication techniques by students; it also aims to verify how these students evaluate the use of the taught contents in the relationship with hospitalized psychiatric patients. An empirical descriptive exploratory research was developed during the second semester of 1999. Nineteen students of a the technical Nursing Course at UFPR (Federal University of Paraná) participated in this study. They were divided in two subgroups: subgroup I was provided with the contents on human communication and therapeutic communication, subgroup II was not. It was verified a higher frequency in the use of therapeutic communication techniques in subgroup I. The students of this subgroup evaluated the taught knowledge on human and therapeutic communication as "optimal", "it facilitates communication", "it enhances assurance", "it brings about the conscious use of knowledge." It can be concluded that the taught contents increased the frequency in the use of communication techniques and were a student-patient communication facilitator.